2008
DOI: 10.1021/ac800751y
|View full text |Cite
|
Sign up to set email alerts
|

Intracavity Optogalvanic Spectroscopy. An Analytical Technique for 14C Analysis with Subattomole Sensitivity

Abstract: We show a new ultrasensitive laser-based analytical technique, intracavity optogalvanic spectroscopy, allowing extremely high sensitivity for detection of (14)C-labeled carbon dioxide. Capable of replacing large accelerator mass spectrometers, the technique quantifies attomoles of (14)C in submicrogram samples. Based on the specificity of narrow laser resonances coupled with the sensitivity provided by standing waves in an optical cavity and detection via impedance variations, limits of detection near 10(-15) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
126
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(131 citation statements)
references
References 26 publications
5
126
0
Order By: Relevance
“…Given that none of these claims were challenged, we must assume that Murnick has conceded them. This again challenges his own claims (Murnick et al 2008), which make no mention of these confounding factors.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Given that none of these claims were challenged, we must assume that Murnick has conceded them. This again challenges his own claims (Murnick et al 2008), which make no mention of these confounding factors.…”
mentioning
confidence: 66%
“…Our theoretical basis is an extension of the model he espoused in his own peer-reviewed publications. Compare what we present against his own model (Murnick et al 2008). We expanded one of his products into an integral and placed rough bounds on his own otherwise unspecified term K, which "is a corresponding optogalvanic proportionality constant that depends on the details of the electric discharge" (Murnick et al 2008).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…where I 0 is the laser intensity,  L is the absorption cross-section of the photon-molecule interaction, lr 2 is the cylindrical volume in the plasma that is exposed to the laser beam, and K is a proportionality parameter accounting for the effects that the physics and chemistry of the plasma have on the signal [13]. Studies have shown that K is not a constant and depends on a variety of parameters [19,20], wherefore Eq.…”
Section: Theorymentioning
confidence: 99%
“…Instead, old technology has been used, and these attempts failed to spark any significant scientific or commercial interest [13,14].…”
Section: Introductionmentioning
confidence: 99%